Optimization of Magetan Police Residential Satrescrim Tipidum Unit Investigators in Revealing the Crime of Increased Theft - Pangestu, Ananda (Advances in Police Science Research Journal, 2024)
Investigators from the Tipidum Unit at the Magetan Police Criminal Investigation Unit have a crucial role in efforts to uncover theft crimes that are disturbing the public. Observing the National Police Chief's Work Program with a vision, namely PRECISE (Predictive, Responsible and Fair Transparency), the National Police are required to be able to anticipate and deal with criminal acts that occur. There is a discrepancy between Das Sein and Das Sollen in terms of the management of the Tipidum unit and the performance of investigators in uncovering cheating cases. This research aims to describe the performance of investigators in uncovering theft cases in the Magetan Police jurisdiction. The research method used is descriptive analytical and qualitative data analysis techniques. The research results show that investigators are not yet optimal in uncovering cases of theft with weights due to obstacles, which consist of human resource aspects and management aspects. For this reason, steps are needed to increase the possibility of disclosing cases by implementing this in the hope that investigators can be more optimal in uncovering criminal acts of theft with weights, thereby creating better security and public order.